Docker for serverless applications : containerize and orchestrate functions using OpenFaas, OpenWhisk, and Fn /: containerize and orchestrate functions using OpenFaas, OpenWhisk, and Fn. (2018) - Kaewkasi, Chanwit
No abstract available